2018
DOI: 10.1038/s41431-018-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo truncating variants in PHF21A cause intellectual disability and craniofacial anomalies

Abstract: Potocki-Shaffer syndrome (PSS) is a contiguous gene syndrome caused by 11p11.2 deletions. PSS is clinically characterized by intellectual disability, craniofacial anomalies, enlarged parietal foramina, and multiple exostoses. PSS occasionally shows autism spectrum disorder, epilepsy, and overgrowth. Some of the clinical features are thought to be associated with haploinsufficiency of two genes in the 11p11.2 region; variants affecting the function of ALX4 cause enlarged parietal foramina and EXT2 lead to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Among three patients with ID and craniofacial anomalies, epilepsy was present in case 1, autism spectrum disorder (ASD) in case 2, and overgrowth with macrocephaly in cases 1 and 3. The authors have concluded that PHF21A haploinsufficiency results in ID and craniofacial anomalies, and possibly contributes to ASD, epilepsy, and overgrowth [8]. Here, we report seven individuals with heterozygous pathogenic sequence variants within the coding region of PHF21A and provide detailed clinical descriptions, further expanding the phenotype associated with PHF21A haploinsufficiency.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Among three patients with ID and craniofacial anomalies, epilepsy was present in case 1, autism spectrum disorder (ASD) in case 2, and overgrowth with macrocephaly in cases 1 and 3. The authors have concluded that PHF21A haploinsufficiency results in ID and craniofacial anomalies, and possibly contributes to ASD, epilepsy, and overgrowth [8]. Here, we report seven individuals with heterozygous pathogenic sequence variants within the coding region of PHF21A and provide detailed clinical descriptions, further expanding the phenotype associated with PHF21A haploinsufficiency.…”
Section: Introductionmentioning
confidence: 71%
“…Although we reported that PHF21A was associated with ID and craniofacial anomalies by the positional cloning of two patients with balanced translocations in 2012 [4], no point mutations affecting this gene had been reported to confirm its deleterious impact until three patients with de novo truncating mutations were reported very recently [8], while this manuscript was being prepared. Taking into account that one out of the three reported patients has ASD [8], we also identified an additional three patients with ASD (patients 1, 5, and 7), further suggesting that PHF21A is a novel ASD gene. Patients 1 and 3 have very similar mutations, differing by only one amino acid, yet only patient 1 has ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In previous works, we reported trigonocephaly, a form of craniosynostosis, in which the early closure of the metopic suture leads to a metopic ridge in patients affected with motor, learning and speech developmental delays 7,8 . In a collaborative work we have recently identified de novo truncating variants in PHF21A in three patients of NDD with macrocephaly and/or trigonocephaly 9 …”
Section: Introductionmentioning
confidence: 94%
“…Eight of those (SCN1A, IQSEC2, STXBP1, CACNA1E, ARID1B, DDX3X, WHSC1, PHF21A) have been known to be responsible for NDDs associated with IDs or epilepsies. 9,[20][21][22][23][24][25][26][27][28][29] The remaining nine (MSX2, CYP1A1, C14orf119, FLI1, CYB5R4, SEL1L2, RAB11FIP2, ZMYND8, and ZNF143) were novel for NDD so far to our knowledge.…”
Section: Identification Of Genes Mutated In Patients With Nddmentioning
confidence: 99%
See 1 more Smart Citation